ADVANCES IN BONE REMODELING AND CLEAR ALIGNERS IN ORTHODONTICS (International Seven Journal of Multidisciplinary, 2024)
The use of clear aligners in orthodontics represents a significant advancement in dental treatment, allowing effective tooth movement with a less invasive approach compared to traditional fixed appliances. Clear aligners not only facilitate the alignment of teeth but also promote changes in the supporting alveolar bone. The success of these movements relies on the surrounding bone's response to mechanical stress during treatment, involving processes of bone resorption and deposition. Research has demonstrated that advancements in digital technology, such as 3D modeling and artificial intelligence, enhance the planning of tooth movements, making bone remodeling more predictable. Sophisticated algorithms simulate aligner forces on the alveolar bone, optimizing each treatment phase. However, limitations persist in complex cases where specific movements, like extrusion and rotation, require precise force control. Recent studies by Guo et al. (2023) and Abogabal et al. (2023) evaluated the effects of clear aligners on alveolar bone dimensions during orthodontic treatment, finding a greater occurrence of bone defects after treatment. They highlighted the differences in bone height changes between aligners and fixed appliances, indicating that clear aligners might have less impact on bone height. Innovative approaches such as low-intensity pulsed ultrasound (LIPUS) and high-frequency vibration (HFV) have also been investigated for their potential to enhance treatment outcomes. Research indicates that daily vibration may reduce the time required for dental correction while increasing levels of cytokines and markers for bone remodeling. Overall, the integration of digital tools and innovative techniques in orthodontics is crucial for improving treatment efficacy, addressing challenges in complex cases, and ultimately enhancing patient experience and satisfaction.